Using tablet computers with elementary school students with special needs: The practices and perceptions of special education teachers and teacher assistants - Johnson, Genevieve Marie (Association for Media and Technology in Education in Canada (A MTE C), 2013)
Twelve special education teachers and teacher assistants who have instructional experience using iPads with children with special needs completed a survey that queried their practices and perceptions. In general, teachers and assistants were extremely positive about the value of iPads for children with special needs, particularly for children with autism, attention deficits and limitations of fine motor control. Special education teachers and teacher assistants reported most frequently using iPads to promote student language and literacy skills, although mathematics learning activities were also commonly reported. Enhanced student motivation was the most frequently reported benefit of using tablet computers in school followed by instructional planning advantages. Teaching tasks might reasonably include downloading and organizing specific applications on specific children's tablets and professional development might increasingly focus of evaluation of tablet applications.